2013
DOI: 10.1103/physreva.87.062503
|View full text |Cite
|
Sign up to set email alerts
|

Transition energies of theDlines in Na-like ions

Abstract: The NIST electron beam ion trap (EBIT) was used to measure the D 1 (3s-3p 1/2 ) and D 2 (3s-3p 3/2 ) transitions in Na-like ions of xenon, barium, samarium, gadolinium, dysprosium, erbium, tungsten, platinum, and bismuth. The wavelengths are in the range 3-12 nm. Relativistic many-body perturbation theory calculations were carried out for the D 1 and D 2 lines for every element in the isoelectronic sequence from argon (Z = 18) to uranium (Z = 92), taking into account some higher-order terms in the quantum elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 46 publications
4
39
1
Order By: Relevance
“…While elements with a high-Z atomic number have these effects amplified, ions in the medium-Z region have special importance because they allow for more accurate experiments and provide constraints to theoretical trends. In the past few years, the electron beam ion trap (EBIT) research program at the National Institute of Standards and Technology (NIST) has reported accurate measurements in the extreme ultraviolet (EUV) region that focus on systematic observations of transitions in L-shell, M-shell and N-shell ions [2][3][4][5][6][7][8][9][10][11][12][13][14]. The work reported here extends these results to a range of previously unobserved transitions of a fifth row element, yttrium.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…While elements with a high-Z atomic number have these effects amplified, ions in the medium-Z region have special importance because they allow for more accurate experiments and provide constraints to theoretical trends. In the past few years, the electron beam ion trap (EBIT) research program at the National Institute of Standards and Technology (NIST) has reported accurate measurements in the extreme ultraviolet (EUV) region that focus on systematic observations of transitions in L-shell, M-shell and N-shell ions [2][3][4][5][6][7][8][9][10][11][12][13][14]. The work reported here extends these results to a range of previously unobserved transitions of a fifth row element, yttrium.…”
Section: Introductionmentioning
confidence: 58%
“…The two most prominent ones are the well-known Na-like D 1 [7]. Gillaspy et al [7] have pointed out that the accuracy of the measurements in medium-Z to high-Z systems is sensitive to the finite nuclear size correction in the otherwise calculable QED terms. This illustrates the importance of these transitions in studies at the interface of atomic and nuclear physics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray spectroscopy utilizing emissions from L-shell as well as M-shell tungsten ions is an attractive option for tokomak plasma diagnostics [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The temperature of the ITER core will be sufficiently high to produce the L-shell tungsten ionic charged states.…”
mentioning
confidence: 99%